Are Cancer Stem Cells a Suitable Target for Breast Cancer Immunotherapy? - Ruiu, Roberto; Di Lorenzo, Antonino; Cavallo, Federica; Conti, Laura (Frontiers in Oncology, 2022)
There is substantial evidence to suggest that complete tumor eradication relies on the effective elimination of cancer stem cells (CSCs). CSCs have been widely described as mediators of resistance to conventional therapies, including chemo- and radiotherapy, as well as of tumor metastasization and relapse in different tumor types, including breast cancer. However, the resistant phenotype of CSCs makes their targeting a tough task, and immunotherapy may therefore be an interesting option. Nevertheless, although immunotherapeutic approaches to cancer treatment have generated great enthusiasm due to recent success in clinics, breast cancer treatment mostly relies on standard approaches. In this context, we review the existing literature on the immunological properties of breast CSC and immunotherapeutic approaches to them. We will thus attempt to clarify whether there is room for the immunotargeting of breast CSCs in the current landscape of breast cancer therapies. Finally, we will provide our opinion on the CSC-targeting immunotherapeutic strategies that could prospectively be attempted.